Makna Hizb dalam Al-Qur’an: Mengungkap Pesan Moral Al-Qur’an tentang Politik Identitas - Syafruddin Syafruddin; Zulheldi Zulheldi; Faizin Faizin; Mukhrin Mukhrin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Meaning of Hizb in the Qur'an: Revealing the Moral Message of the Qur'an about Identity PoliticsThis article discusses the moral message of the Qur'anic verses about hizb in relation to identity politics. This study is motivated by the use of the term hizb which is not in line with the moral message of the Koran and tends to be misused for the benefit of power politics. To reveal the moral message of the Koran used qualitative research by making the verses of the Koran about hizb as the object of study. Al-Qur'an verses about hizb are described thematically with the double movement theory approach, Fazlur Rahman. The results of this study indicate that the verses about hizb imply a moral message that is directly related to identity politics, especially the relationship between the existence of human plurality and divine principles. This relationship is formed by the existence of religiosity which supports the maintenance of ethical values. In addition, progressive ideas born from a nation's democracy always rest on ethical and rational truths. Ethical truth directs people consciously to maintain their identity without ignoring rational truth. Meanwhile, rational truth is placed properly in maintaining national unity in the discourse of democracy